The model of corporate social responsibility in project management - Schieg, Martin (Business: Theory and Practice, 2009)
Corporate social responsibility as a management concept is growing more and more important also for project companies. The task of project management is to identify relevant ecological systems, to recognize the internal and external dimension of social responsibility, and to test existing standards of Corporate Social Responsibility for their applicability in projects. The special benefit of CSR in projects is to set-up values such as integrity, credibility and reputation. For successful implementation of CSR activities, it is essential to align the commitment of the project organization to the own business operations and own goals. Įmonių socialinės atsakomybės vadybos modelis Santrauka. Įmonių socialinės atsakomybės koncepcija tampa vis svarbesnė. Projektų vadybos tikslas – nustatyti svarbias ekologines sistemas, suvokti vidinius ir išorinius socialinės atsakomybės aspektus, patikrinti verslo socialinės atsakomybės standartus. Įmonių socialinės atsakomybės nauda – sukurti tokias vertybes, kaip dorumas, patikimumas ir reputacija. Reikšminiai žodžiai: socialinė korporacijos atsakomybė, darnioji plėtra, socialinė atsakomybė, projektų valdymas, darniosios plėtros trimatis pagrindas. First Published Online: 10 Dec 2009